FACTORS INFLUENCING TOURIST’S INTENTION TO SELECT A TOURISM DESTINATION BY USING SOCIAL MEDIA - Fairuz Abd Hakim; Chemah Tamby Chik; Fasihah Abdul Latiff; Suria Sulaiman (Journal of Islamic, Social, Economics and Development, 2022)
Today, there are tons of social media websites such as Facebook, Instagram, Twitter,and YouTube that can help tourists to find and decide the best tourism destination for theirvacations. Despite the growing interest in social media platforms, tourists have an issue withthe credibility of social media. In the tourism context, past studies have proposed that socialmedia can increase people's awareness of destination and information search. However, itsrelative influence on destination selection is still unclear. Because of this, the question of thecredibility or reliability of internet travel and tourism information sources has remainedarguable. The objective of this study is to examine the factors influencing tourist intention toselect a tourism destination by using social media in Malaysia. This study focuses on two majorfactors of social media- social media information and social media word-of-mouth (WOM). Theunit of analysis is individual and the sample population are experienced tourists aged 20 to 59in Malaysia. Three hundred ninety (390) questionnaires were successfully collected throughonline platform. The data were analyzed using Statistical Package for the Social Sciences(SPSS) software version 28.0. The findings revealed that all factors suggested have significantrelationships with tourist travel intention from the experienced tourist point of view, providinga better understanding for tourists in Malaysia in using social media when planning a vacation.The existence of social media in marketing strategies made it possible for the industry to offercustomers sufficient and essential information with knowledge for their choice of destinations.